PERANAN BUDAYA, BAHASA, DAN SASTRA DALAM MENUMBUHKAN TOLERANSI DAN SIKAP SALING MENGHORMATI - Maman S Mahayana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Indonesian literature culturally is essentially 'ethnic' literature. The use of Indonesian language that places it as Indonesian literature, a national language derived from the Malay ethnic language. As a literature whose spirit is derived from ethnic culture, it can not be separated from the things that circle it. However, the creation of literary works does not come from emptiness. Not taken by angels from the sky. Literature was born from various socio-cultural problems, ideology, and so on which became anxiety writers. Indonesian literature is culturally an 'ethnic' literature so the study of it, directly or indirectly, can be used as an entry point to introduce the wealth of other ethnic cultures. Thus, literary learning in schools should no longer be treated as theoretical knowledge, but as a form of appreciation of the literary treasures of Indonesia itself and all as an effort to introduce ethnic culture with various phenomenon